2007
DOI: 10.1038/sj.onc.1210298
|View full text |Cite
|
Sign up to set email alerts
|

The Shb signalling scaffold binds to and regulates constitutive signals from the Epstein–Barr virus LMP2A membrane protein

Abstract: The Epstein-Barr virus latency-associated membrane protein LMP2A has been shown to activate the survival kinase Akt in epithelial and B cells in a phosphoinositide 3-kinase-dependent fashion. In this study, we demonstrate that the signalling scaffold Shb associates through SH2 and PTB domain interactions with phosphorylated tyrosine motifs in the LMP2A N-terminal tail. Additionally, we show that mutation of tyrosines in these motifs as well as shRNA-mediated downregulation of Shb leads to a loss of constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…ITAM is required for association with Syk, which provides B cells with survival signals, including PI3K and ERK activation (14,49). A recent study demonstrated that Shb, which is recruited to ITAM, is involved in the regulation of PI3K activity by LMP2A (50). The present study demonstrated that ITAM is also required for ERK-dependent anoikis resistance mediated by LMP2A in epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
“…ITAM is required for association with Syk, which provides B cells with survival signals, including PI3K and ERK activation (14,49). A recent study demonstrated that Shb, which is recruited to ITAM, is involved in the regulation of PI3K activity by LMP2A (50). The present study demonstrated that ITAM is also required for ERK-dependent anoikis resistance mediated by LMP2A in epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
“…LMP2A mimics BCR signaling and is important for EBV latency and virus-induced oncogenesis (Fotheringham et al, 2012; Scholle et al, 2000; Swart et al, 2000). LMP2A associates with Syk and Lyn tyrosine kinases and with scaffold protein Shb to activate Ras, PI3K and Akt (Fukuda and Longnecker, 2007; Matskova et al, 2007; Swart et al, 2000). The ITAM motif of LMP2A is required for activation of Akt (Morrison and Raab-Traub, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SHB becomes tyrosine-phosphorylated upon stimulation of the PDGF receptors, FGFR1, T cell receptor, VEGFR2, c-Src-family kinases, EphB2 and the angiogenesis inhibitor endostatin. SHB also binds the growth hormone receptor (Moutoussamy et al 1998) and the Epstein-Barr virus protein LMP2A (Matskova et al 2007), of which the latter causes SHB tyrosine phosphorylation by Syk and Lyn (Dergai et al 2013), thus participating in viral responses (Arbiser 2015). In addition, SHB associates with the tyrosine phosphatase SHP-2 (PTPN11; protein tyrosine phosphatase, non-receptor 11) via unknown mechanism(s) .…”
Section: Introductionmentioning
confidence: 99%